Consultation, commissions and context : a comparative study of the Law Commission and the Australian Law Reform Commission - White, B (2004)
This thesis compares the consultation conducted by the Law Commission ('LC') and the Australian Law Reform Commission ('ALRC'). Its first goal is to describe the process in detail, which begins with the purposes of consultation. Next, the process of consultation is described with a discussion of each of the techniques employed by the Commissions. Although there is much overlap in how the LC and the ALRC consult, they do approach the exercise differently and these differences are discussed. The description of the Commissions' consultation concludes by examining its impact. A second goal is to compare the two Commissions' approach to consultation and this comparison is aided by the development of two models: the English Commission's expert model of consultation and the Australian Commission's more inclusive model. Underpinning the comparison between the two Commissions and these different models is the intended target of the consultation exercise. It is argued that the LC's decisions are motivated by the goal of securing expertise, more than is the case at the ALRC. By contrast, the Australian Commission is influenced more than is its English counterpart by a desire to include as many consultees as possible. An important part of this comparative study is to explain why the two Commissions consult differently. The most significant reasons are the history of two Commissions, especially the role of the founding Chairmen, and the types of projects that the Commissions undertake. A third goal, albeit only a tentative one, is to suggest ways in which the Commissions could improve their consultation. These comments are scattered throughout the thesis, but one theme that emerged was that there seems to be insufficient thought given to a number of important stages in the consultation process.